Yca1 metacaspase: diverse functions determine how yeast live and let die. (31st March 2023) - Lam, Darren K; Sherlock, Gavin
Abstract: The Yca1 metacaspase was discovered due to its role in the regulation of apoptosis in Saccharomyces cerevisiae . However, the mechanisms that drive apoptosis in yeast remain poorly understood. Additionally, Yca1 and other metacaspase proteins have recently been recognized for their involvement in other cellular processes, including cellular proteostasis and cell cycle regulation. In this minireview, we outline recent findings on Yca1 that will enable the further study of metacaspase multifunctionality and novel apoptosis pathways in yeast and other nonmetazoans. In addition, we discuss advancements in high-throughput screening technologies that can be applied to answer complex questions surrounding the apoptotic and nonapoptotic functions of metacaspase proteins across a diverse range of species. Abstract : The Yca1 metacaspase contributes to both cellular health and regulated cell death in yeast through its multiple functions in apoptosis, proteostasis, and cell cycle regulation.